Intrinsic versus extrinsic cues as determinants of perceived product quality. - Szybillo, George J.; Jacoby, Jacob (Journal of Applied Psychology, 1974)
This study tested a portion of Olson's cue model which hypothesizes that, other things equal, intrinsic cues (e.g., physical product differences) will be stronger determinants of perceived-qua lity judgments than will extrinsic cues (e.g., price or store image). Ninety female undergraduates were randomly assigned to the conditions of a 2X3X3 (Price X Store Image X Hosiery Product Samples) analysis of variance with repeated measures on the intrinsic factor. Results supported the hypothesis; omega-square values revealed that 73% of the total variance was due to intrinsic product sample differences. Additionally, Shapiro's hypothesis that perceived worth would be more strongly related to stated purchase intentions than would perceived quality was supported. Purchase behavior in contemporary American society requires, among other things, that the consumer be able to make judgments and comparisons across products, brands, and services. Such judgments are arrived at by a process in which some or all of the various items of information (i.e., cues) associated with the product, brand, or service are identified, evaluated, and integrated to form a composite judgment. One judgment usually of considerable importance to the consumer is the product's quality, and more than a score of published studies have examined the effects of specific cues on the judgment of perceived quality (cf. Jacoby, Olson, & Haddock, 1971; Olson, 1972). Little thought, however, has been given to developing a conceptual framework for expressing how and when specific cues or types of cues operate to form the composite quality judgment. Until recently, the most notable exception has been Cox (1962), who developed a cue-processing model based upon the notions of predictive and confidence value. Other investigators (Jacoby et al., 1971; Valenzi & Andrews, 1971) have distinguished between intrinsic and extrinsic cues. The former refer to cues which, if changed, would produce a resultant change in the physical product itself (e.g., flavor and aroma cues for beer), while the latter refer to such factors